(untitled) (Vietnam Journal of Community Medicine, 2021)
The study was designed according to descriptive epidemiological research through an analytical cross-sectional investigation. Directly interviewing 434 male students of joint medicine at Thai Binh University of Medicine and Pharmacy in 2020. Research results: Describe knowledge of tobacco harm prevention and control of male students of Thai Binh University of Medicine and Pharmacy in 2020. Research shows that: The majority of study subjects (96.6% -98.9%) know that smoking cigarettes or passive smoking all affects their health. However, still 1.1% - 3.4% still do not know the harms of smoking. There are 88.9% of subjects who know about the law on tobacco harm prevention and control. Proportion of study subjects with correct knowledge of completely non-smoking places in the house and within the campus is from 79.3% -93.8%.